Dancing with giants : (World Bank, Institute of Policy Studies, 2007)
The predicted growth of the Indian and Chinese economies, with their massive populations, portends important implications for the rest of the world. In this volume, Winters (director, Development Research Group, World Bank) and Yusuf (economic adviser, Development Research Group, World Bank) present seven chapters that explore some of these implications. Two chapters model growth patterns into the future for the Asian "Giants" and analyze the model's outputs regarding flows of goods and services, the structure of production, economic welfare, and energy/emissions scenarios. Other chapters take a less quantitative approach, with authors describing current and foreseeable developments in industrial capability; reviewing the evidence on poverty reduction, inequality, and economic growth; and examining trends in governance and the investment climate